Garga and Early Astral Science in India - Geslani, Marko; Mak, Bill; Yano, Michio; Zysk, Kenneth (History of Science in South Asia)

(untitled) (University of Alberta Library, 2017)
This article forms a preliminary report on the work by an international group of scholars on Garga, an important early authority on astral science (jyotiṣa). Reviewing past research on the texts associated with this figure, we focus especially on the earliest text, the Gārgīyajyotiṣa (ca. first century CE?), a compendium of material on astral and terrestrial omens, ritual, horoscopy, and astronomy, that prefigures Varāhamihira's well-known Bṛhatsaṃhitā. The contributions include text-critical observations based on select chapters, remarks on astral omens and their relevance to the possible dating of the text, and a discussion of the text's potential for the study of Hindu ritual. The article also begins to disambiguate the broader Garga corpus by including a chapter summary of a somewhat later Gargasaṃhitā, containing mainly astronomical materials.